Produksi Media Pembelajaran Digital sebagai Upaya Penguatan Kompetensi Guru di Madrasah Ibtidaiyah - Zinde Ulfa Ramadhona; Zahrah Muslimah (Sagita Academia Journal, 2026)
This study aims to analyze the production of digital learning media as an effort to strengthen teacher competence in Madrasah Ibtidaiyah. The rapid development of technology in education requires teachers to be able to create innovative, interactive, and effective learning media to support the learning process. However, many teachers still face challenges in utilizing digital technology due to limited skills and understanding in developing learning media. This research used a qualitative descriptive method through observation, interviews, and documentation to obtain data related to the implementation of digital learning media production among Madrasah Ibtidaiyah teachers. The results of the study indicate that the production of digital learning media can improve teachers’ pedagogical and professional competence, especially in designing creative learning, increasing students’ motivation, and creating more interactive classroom activities. In addition, the use of digital media also helps teachers adapt to technological developments and supports more effective learning processes. Therefore, digital learning media production can be an important strategy in strengthening teacher competence in Madrasah Ibtidaiyah and improving the quality of education in the digital era.